Heat integration between CO2 Capture and Liquefaction and a CHP Plant: Impact on Electricity and District Heating Delivery at Renova’s CHP Plant in Sävenäs - Hammar, Caroline (My University, 2022)
Carbon capture and storage (CCS) is an important technology for emissions difficult to mitigate with fuel-switching or electrification - like emissions from waste incineration. However, an installation of CO2 capture to a combined heat and power (CHP) plant may result in a substantial decrease in electricity and district heating (DH) delivery. This thesis evaluates the effects on electricity and DH delivery of an integrated capture and liquefaction plant treating 60% of the flue gases from Renova’s waste-to-energy (WTE) CHP plant in Sävenäs. Two CO2 absorption technologies, monoethanolamine (MEA) or hot potassium carbonate (HPC) based, are evaluated with respect to the practical constrains of the CHP plant. The heat integration evaluated possibilities for the heat extraction from the CHP plant to drive the capture plant, as well as the possibilities for recovery of heat from the capture and liquefaction to the district heating system in the CHP plant. The work concludes that the CHP plant with an integration to a capture and liquefaction plant utilizing HPC deliver more DH compared to the current delivery without CCS implementation. However, HPC also entails a significant reduction in electricity delivery compared to current levels. The MEA based process delivers a similar amount DH as the current levels and has a lower electricity loss than the HPC process. CCS operation during the summer season requires an investment in additional cooling capacity of 28.3 MW for MEA and 23.2 MW for HPC. Therefore, it is recommended to perform an economic analysis of the option to solely operate the CCS plant during the winter season. Furthermore, the work highlight the broad spectra of effects on the local energy system of a CCS integration - the resulting effect on electricity delivery was 48- 88% of the retained electricity delivery and the resulting district heating delivery was 99-116% of the current delivery. The choice of solvent, heat source for solvent generation, level of CCS heat recovery, and possibility for heat pumping are all important aspects for the CCS integration.
Keywords: CCS; CHP; Waste-to-energy; Heat recovery